2009
DOI: 10.4314/wajm.v28i3.48480
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts in the Diagnosis of Primary Open Angle Glaucoma

Abstract: BACKGROUND: Primary open angle glaucoma is characterized by quantifiable parameters including the intraocular pressure, the aqueous outflow facility, and geometric measurements of the optic disc and visual defects. Despite this, diagnosis remains controversial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Although an elevated IOP is a significant risk factor for the development of glaucoma, it is important to note that sight-threatening effects of glaucoma are not necessarily coming from increased IOP but from retinal and optic nerve neurodegeneration. There are examples of patients that have normal pressure glaucoma (NPG), as well as patients with no retinal damage that have chronically high IOP [23][24][25] . Even in a DBA/2J mouse, a model for secondary angle-closure glaucoma, it has been shown that hypertension is not the only causative factor in glaucomatous optic neuropathy 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Although an elevated IOP is a significant risk factor for the development of glaucoma, it is important to note that sight-threatening effects of glaucoma are not necessarily coming from increased IOP but from retinal and optic nerve neurodegeneration. There are examples of patients that have normal pressure glaucoma (NPG), as well as patients with no retinal damage that have chronically high IOP [23][24][25] . Even in a DBA/2J mouse, a model for secondary angle-closure glaucoma, it has been shown that hypertension is not the only causative factor in glaucomatous optic neuropathy 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Estrogens play an important role in angiogenesis, ensuring vasodilation and preparing for uterine contraction, in addition to promoting catabolic metabolism and enlargement of the mammary glands. Since the gestational period is related to physiological, pathological changes or modifications of certain conditions, we have to take into account the tissue changes that may occur (OMOTI, et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Health insurance needs to be restructured to accommodate all citizens irrespective of their job status. A simple and systematic approach in examination will improve accurate diagnosis of glaucoma [61] and provide basis for appropriate management. Preventing glaucoma blindness in low income economy is a hard task, but it is never late to start.…”
Section: Treatment Of Poagmentioning
confidence: 99%